ΤΟ ΡΩΣΙΚΟ ΤΑΞΙΔΙ TOΥ ΑΘΑΝΑΣΙΟΥ ΠΑΤΕΛΛΑΡΟΥ ΚΑΙ Ο «ΠΡΟΤΡΕΠΤΙΚΟΣ ΛΟΓΟΣ» TOΥ ΠΡΟΣ ΤΟΝ ΤΣΑΡΟ ΑΛΕΞΙΟ (1653) - ΑΛΕΞΑΝΔΡΟΠΟΥΛΟΥ, ΟΛΓΑ (Μνήμων, 1999)
Olga Alexandropoulos, Athanasios Patellaros' voyage to Russia and his«Impelling Oration» to Aleksej Mikhajlovich, Tsar of Russia (1653) The paper is concerned with the last, short-term still significant periodof Ath. Patellaros' life, which he spent in Russia, and aims to broadenthe framework, in which Patellaros is usually referred to: as a welleducated Greek scholar, known mostly due to his two rather scandalousascensions to the patriarchal seat of Constantinople, his contacts withthe Western church and his friendly relations with Vassilios Lupu, thehospodar of Wallachia.In the first part, Russian archival sources referring to Patellaros1voyage to Moscow are presented. The Oration, poorly known as it ispreserved only in a contemporary, unpublished Russian translation, isdiscussed in the second part as an important monument of Greek-Russianrelations during the 17th c, as well as a noteworthy sample ofGreek appeals to foreign rulers for liberation from the Turkish yoke.